Augsburg commentary on the New Testament : Mark - Juel, Donald H. (Donald Harrisville) (Minneapolis Augsburg, 1990)
The Augsburg Commentary on the New Testament Series (ACNT) is written for laypeople, students, and pastors. Laypeople will use it as a resource for Bible study at home and at church. Students and instructors will read it to probe the basic message of the books of the New Testament. And pastors will find it to be a valuable aid for sermon and lesson preparation.
Foreword -- Abbreviations -- Introduction -- Outline -- Commentary -- Selected Bibliography
Includes bibliographical references (pages 237-238).
Keywords: Bible. -- Commentaries